A gradient‐extended damage‐plasticity model to counteract mesh dependence in finite element simulations. Issue 1 (15th March 2018) - Brepols, Tim; Wulfinghoff, Stephan; Reese, Stefanie
Abstract: This study is concerned with theoretical and numerical aspects of a thermodynamically consistent gradient‐extended damage‐plasticity model which is based on a 'two‐surface' approach: damage and plasticity are treated as, in principle, independent physical mechanisms by using separate yield and damage criteria as well as individual sets of loading / unloading conditions. Such a model is especially appealing from a practical point of view since it can naturally account for various situations in which the model's behavior is either (quasi‐)brittle‐like, ductile‐like or possibly anything in between. The model's algorithmic treatment at the local integration point level requires special considerations. In this regard, two inherently different strategies are implemented and tested during the study and are briefly discussed here. A numerical benchmark test reveals that the proposed gradient‐extended damage‐plasticity model is well suited for counteracting the results' mesh size dependence in finite element simulations involving damage. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)